Placental Growth Factor Levels in Preeclampsia Compared to Normal Pregnancy - Situmorang, Dumaria; Tendean, Hermie MM; Wantania, John J (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To identify and analyze the differences in the levels of PlGF in preeclampsia and normal pregnancy. Method: This was a cross-sectional observational qualitative study of PlGF in preeclampsia and normal pregnancy. The number of samples in case and control group was 30 in each groups. Result: We found that mean of maternal age in the preeclampsia group was 28.53 years and 25.23 years in the control group. Mean parity in preeclampsia and control group was 2.33 and 1.56, respectively. Mean hemoglobin level in preeclampsia and control group was 11.97 and 11.99, respectively. Mean maternal blood glucose level was 87.0 in the preeclampsia group, and 87.9 in the control group. In the preeclampsia group mean urea concentration was 16.45, while it was 22.78 in the control group. Mean creatinine level was 0.92 in the preeclampsia group and 0.64 in the control group. Mean SGPT and SGOT in the preeclampsia group was 23.36 and 21.97, while in the control group was 29.86 and 26.20. Test results showed that PlGF levels was significantly different between the preeclampsia and control group. Mean PlGF in the preeclampsia and control group was 42.10 and 452.33 respectively, with p